FAKTOR-FAKTOR YANG MEMENGARUHI KOMPETENSI PENYULUH PERTANIAN DALAM PELAKSANAAN SEKOLAH LAPANG DI KABUPATEN SIJUNJUNG - Yarnismayeni, Yarnismayeni; Tanjung, Hery Bachrizal; Madarisa, Fuad (Agros Journal of Agriculture Science, 2024)
Agricultural extension workers have an important role in increasing farmers' skills and knowledge. One of the lessons in agricultural extension is field school. Field schools becomes knowledge transfer centers for agricultural educators to pass on skills to farmers. In Sijunjung Regency there are four sub-districts that conduct the highest number of field schools which are the focus of research to analyze the factors that influence the competency of agricultural instructors in implementing field schools. This research uses a survey to collect data from agricultural instructors who have implemented field schools since 2016, with a sample of 40 people who have fulfilled the requirements for SEM Partial Least Square (SEM-PLS) analysis using the SmartPls 4.0 program. The results of the research show that factors that have a significant influence on the competency of instructors in implementing field schools in Sijunjung Regency include: the instructor's work environment (including organizational structure, infrastructure, workload, collaboration with partners) and field school learning groups (number of groups, management learning).